2022
DOI: 10.1002/pi.6371
|View full text |Cite
|
Sign up to set email alerts
|

Tri‐layered alginate/poly(𝜀‐caprolactone) electrospun scaffold for cardiac tissue engineering

Abstract: Novel tri‐layered electrospun alginate–graphene oxide (GO)/poly(ε‐caprolactone) (PCL) conductive scaffolds were fabricated with a sequential electrospinning method for the first time, in which the middle PCL layer acts as a mechanical support of the scaffold. The top and bottom alginate–GO nanofibrous layers provide cell viability and attachment, and also electroconductivity for the scaffold. The fabrication of this nanofibrous scaffold aims to simulate cardiac extracellular matrix. Scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Simultaneously, a high level of biocompatibility (viability, adhesion, and proliferation) was demonstrated against cardiac progenitor cells. 54 Numerous studies focused on the positive influence of graphene and its derivatives (GO and rGO) on the bioactivity of biodegradable polymers in tissue engineering and cell delivery applications.…”
Section: Conductive Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, a high level of biocompatibility (viability, adhesion, and proliferation) was demonstrated against cardiac progenitor cells. 54 Numerous studies focused on the positive influence of graphene and its derivatives (GO and rGO) on the bioactivity of biodegradable polymers in tissue engineering and cell delivery applications.…”
Section: Conductive Compositesmentioning
confidence: 99%
“…In the meantime, a number of studies have highlighted the effect of GO on rapid degradability and improved mechanical properties of electrospun polymer scaffolds (such as PCL and alginate) even at extremely low GO content levels (below 1%) compared to pure polymer scaffolds. Simultaneously, a high level of biocompatibility (viability, adhesion, and proliferation) was demonstrated against cardiac progenitor cells 54 . Numerous studies focused on the positive influence of graphene and its derivatives (GO and rGO) on the bioactivity of biodegradable polymers in tissue engineering and cell delivery applications.…”
Section: Conductive Compositesmentioning
confidence: 99%
“…The overall results confirmed that the incorporation of GO into the alginate nanofibers enhanced cell adhesion, viability, and proliferation. In conclusion, the three-layered nanofibrous scaffold made of alginate, graphene oxide, and PCL could be considered a promising biomaterial for cardiac tissue regeneration [ 89 ].…”
Section: Applications Of Alginate In Cvdsmentioning
confidence: 99%
“…In the production of nanofibers, biodegradable polymers such as polyurethane (PU) and poly(ε-caprolactone) (PCL) in composite or with surface modification are most commonly used. Most investigations focus on studying the influence of nanofibrous structure on cardiac cell attachment, viability, maturation, morphology, and orientation [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Tomecka et al compared the viability and alignment of rat cardiomyoblasts (H9c2), neonatal rat CMs (NRCMs), and human CMs, which were cultured on PU nanofibrous materials modified by various proteins (such as COL, poly-l-lysine, gelatin, laminin, and fibronectin).…”
Section: Introductionmentioning
confidence: 99%